Long-term Oncological Outcome of Segmental Versus Extended Colectomy for Colorectal Cancer in Crohn's Disease: Results from an International Multicentre Study. (13th December 2021) - Sensi, Bruno; Khan, Jim; Warusavitarne, Janindra; Nardi, Alessandra; Spinelli, Antonino; Zaghiyan, Karen; Panis, Yves; Sampietro, Gianluca; Fichera, Alessandro; Garcia-Granero, Eduardo; Espin-Basany, Eloy; Konishi, Tsuyoshi; et al.
Abstract: Background and Aims: Crohn's disease increases colorectal cancer risk, with high prevalence of synchronous and metachronous cancers. Current guidelines for colorectal cancer in Crohn's disease recommend pan-proctocolectomy. The aim of this study was to evaluate oncological outcomes of a less invasive surgical approach. Methods: This was a retrospective database analysis of Crohn's disease patients with colorectal cancer undergoing surgery at selected European and US tertiary centres. Outcomes of segmental colectomy were compared with those of extended colectomy, total colectomy, and pan-proctocolectomy. Primary outcome was progression-free survival. Secondary outcomes included overall survival, synchronous and metachronous colorectal cancer, and major postoperative complications. Results: Ninety-nine patients were included: 66 patients underwent segmental colectomy and 33 extended colectomy. Segmental colectomy patients were older [ p  = 0.0429], had less extensive colitis [ p  = 0.0002] and no preoperatively identified synchronous lesions [ p  = 0.0109]. Median follow-up was 43 [31–62] months. There was no difference in unadjusted progression-free survival [ p =  0.2570] or in overall survival [ p  = 0.4191] between segmental and extended colectomy. Multivariate analysis adjusting for age, sex, ASA score, and AJCC staging, confirmed no difference for progression-free survival (hazard ratio [HR] 1.00, p =  0.9993) or overall survival [HR 0.77, p  = 0.6654]. Synchronous and metachronous cancers incidence was 9% and 1.5%, respectively. Perioperative mortality was nil and major complications were comparable [7.58% vs 6.06%, p  = 0.9998]. Conclusions: Segmental colectomy seems to offer similar long-term outcomes to more extensive surgery. Incidence of synchronous and metachronous cancers appears much lower than previously described. Further prospective studies are warranted to confirm these results.